Dario Argento e l’enfasi della visualità - Bisogno, Anna (Scenari, 2021)
Like the true art that knows how to express and anticipate social changes, so Dario Argento’s films, with its empty and threatening streets, oppressive music, tension, blood and terror, represented the mood of Italy to starting from the years. His narrative figure was immediately clear: a strong emphasis on visuality in which different styles are mixed, altering the traditional patterns imposed by the taste of cinema. Argento uses the camera in an elaborate way, combining it with light effects and soundtracks that represent the true quintessence of his work and the perfect background for strong and impressive scenes. It is no coincidence that one considers it to be the european master of the concept of macabre, in which images of violence reach the extreme limit of their expressive capacity. The Roma Tre Film Festival was an opportunity to pay tribute to his art, his career and a period, 1968, when he went out to the cinema – among others – C’era una volta il West for directing Sergio Leone and of whom Argento was one of the subject actors together with Bernardo Bertolucci.